Impact of Cerebral Small Vessel Disease on Functional Recovery After Intracerebral Hemorrhage. Issue 10 (October 2019) - Uniken Venema, Simone M.; Marini, Sandro; Lena, Umme K.; Morotti, Andrea; Jessel, Michael; Moomaw, Charles J.; Kourkoulis, Christina; Testai, Fernando D.; Kittner, Steven J.; Brouwers, H. Bart; James, Michael L.; Woo, Daniel; et al.
Abstract : Background and Purpose—: In this study, we aim to investigate the association of computed tomography–based markers of cerebral small vessel disease with functional outcome and recovery after intracerebral hemorrhage. Methods—: Computed tomographic scans of patients in the ERICH study (Ethnic and Racial Variations of Intracerebral Hemorrhage) were evaluated for the extent of leukoaraiosis and cerebral atrophy using visual rating scales. Poor functional outcome was defined as a modified Rankin Scale (mRS) of ≥3. Multivariable logistic and linear regression models were used to explore the associations of cerebral small vessel disease imaging markers with poor functional outcome at discharge and, as a measure of recovery, change in mRS from discharge to 90 days poststroke. Results—: After excluding in-hospital deaths, data from 2344 patients, 583 (24.9%) with good functional outcome (mRS of 0–2) at discharge and 1761 (75.1%) with poor functional outcome (mRS of 3–5) at discharge, were included. Increasing extent of leukoaraiosis ( P for trend, 0.01) and only severe (grade 4) global atrophy (odds ratio, 2.02; 95% CI, 1.22–3.39, P =0.007) were independently associated with poor functional outcome at discharge. Mean (SD) mRS change from discharge to 90-day follow-up was 0.57 (1.18). Increasing extent of leukoaraiosis ( P for trend, 0.002) and severe global atrophy (β [SE], −0.23 [0.115]; P =0.045) were independently associated with less improvement in mRS from discharge to 90 days poststroke. Conclusions—: In intracerebral hemorrhage survivors, the extent of cerebral small vessel disease at the time of intracerebral hemorrhage is associated with poor functional outcome at hospital discharge and impaired functional recovery from discharge to 90 days poststroke.